2005
DOI: 10.1128/aac.49.8.3171-3177.2005
|View full text |Cite
|
Sign up to set email alerts
|

Fluconazole MIC and the Fluconazole Dose/MIC Ratio Correlate with Therapeutic Response among Patients with Candidemia

Abstract: We tested 32 Candida isolates recovered in the early 1990s from the bloodstreams of patients with candidemia for in vitro susceptibility to fluconazole and determined if MIC and/or the daily dose of fluconazole/MIC ratio correlated with the response to therapy. This is a unique data set since 87.5% (28/32) of patients were treated with fluconazole doses now considered to be inadequate (<200 mg), which contributed to high therapeutic failure rates (53% [17/32]). The geometric mean MIC and dose/MIC ratio for iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
115
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(124 citation statements)
references
References 35 publications
(47 reference statements)
5
115
0
4
Order By: Relevance
“…However, as shown in the present study, resistance to fluconazole among isolates of C. glabrata is not predictable, and therefore antifungal susceptibility testing is needed to ensure optimal antifungal treatment of C. glabrata BSI (7,21,29,59). Indeed, several authors have now demonstrated the importance of the relationship between the daily dose of fluconazole and the in vitro susceptibility of the organisms to fluconazole as a predictor of therapeutic success or failure (4,10,18,29). Baddley et al (10) recently demonstrated that a fluconazole area under the concentration curve-to-MIC ratio of Ͻ11.5 or a MIC of Ն64 mg/ml was associated with increased mortality among patients with candidemia treated with fluconazole.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…However, as shown in the present study, resistance to fluconazole among isolates of C. glabrata is not predictable, and therefore antifungal susceptibility testing is needed to ensure optimal antifungal treatment of C. glabrata BSI (7,21,29,59). Indeed, several authors have now demonstrated the importance of the relationship between the daily dose of fluconazole and the in vitro susceptibility of the organisms to fluconazole as a predictor of therapeutic success or failure (4,10,18,29). Baddley et al (10) recently demonstrated that a fluconazole area under the concentration curve-to-MIC ratio of Ͻ11.5 or a MIC of Ն64 mg/ml was associated with increased mortality among patients with candidemia treated with fluconazole.…”
Section: Resultsmentioning
confidence: 76%
“…In institutions that have lower rates of infection with C. glabrata or in patients for whom infection due to fluconazole-resistant C. glabrata is less likely, fluconazole may still be appropriate as initial therapy for patients who are not critically ill and do not have prior fluconazole exposure (56)(57)(58)80). In such settings, however, it is important to pay strict attention to the appropriate utilization of fluconazole (10,18,29,41,59,90).…”
Section: Resultsmentioning
confidence: 99%
“…Fluconazole is the first drug of choice for the treatment of vaginitis in most parts of the world in accordance with recommended guidelines (Maertens, 2004). However, fluconazole resistance has been reported in both C. albicans and non-albicans species (Clancy et al, 2005;Liu et al, 2009). Approximately 11.5% of the isolates identified as C. albicans were found to be susceptible (in a dose-dependent manner), and 12 isolates were found to be resistant, to fluconazole.…”
Section: Discussionmentioning
confidence: 99%
“…The yeast C. albicans is the most common source of nosocomial bloodstream infections (4), mostly associated with the use of medical devices. FLC is often used to treat acute or chronic vaginal candidiasis and fungal infections in hospitalised patients or to prevent fungal infections in AIDS patients (27)(28)(29). However, the number of azoleresistant, mainly non-C. albicans isolates has increased in hospital care (30), limiting its application.…”
Section: Discussionmentioning
confidence: 99%